Pelatihan Penulisan Buku dan Nama Samaran - Tomy Michael (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The pseudonym given by Law No. 3-2017 will present a dilemma for lecturers in producing scientific books obtained at the National Library. Activities carried out with careful planning, activities carried out and the results of discussions about what will be written in books and popular articles that can be written by the participants. Training activities essentially provide an understanding of the rights and obligations of special authors in pseudonyms. Popular themes for lecturers with ISI, ASBI and Popular Article themes.